Outcome of monochorionic twin pregnancies with moderate amniotic fluid discordance adjoining twin–twin transfusion syndrome†. (25th January 2016) - Hayashi, Satoshi; Anami, Ai; Ishii, Keisuke; Oba, Mari S.; Takahashi, Yuichiro; Nakata, Masahiko; Murotsuki, Jun; Murakoshi, Takeshi; Sago, Haruhiko
Abstract: Objectives: This study aimed to assess the perinatal outcome in monochorionic diamniotic (MD) twin pregnancies complicated by amniotic fluid discordance (AFD) adjoining twin–twin transfusion syndrome (TTTS). Methods: An observational study of 84 consecutive MD twin pregnancies complicated by AFD that resembled TTTS was conducted. AFD adjoining TTTS was defined by a maximal vertical pocket of amniotic fluid ≤3 cm in one twin and ≥7 cm in the other excluding TTTS. The study population was divided into two groups, group 1 and group 2, according to positive and absent or reversed end‐diastolic flow (AREDF) in the umbilical artery, respectively. Results: Fifteen of the 35 (42.9%) group 1 cases and 30 of the 49 (61.2%) group 2 cases progressed to TTTS. The overall survival and intact survival rate in constant AFD that never progressed to TTTS in group 1 was 100% (40/40) and 90% (36/40), respectively. The overall survival and intact survival rate of constant AFD in group 2 with selective intrauterine growth restriction (sIUGR) was 54.2% (13/24) and 41.7% (10/24), respectively, and for those without sIUGR was 64.3% (9/14) and 57.1% (8/14), respectively. Conclusions: Constant AFD with AREDF in the umbilical artery represents an extremely high risk for adverse outcomes regardless of the presence of sIUGR. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Monochorionic diamniotic twin pregnancies presenting prenatally with moderately discordant amniotic fluid volumes are at an increased risk of the later development of TTTS or sIUGR. Cases of sIUGR with abnormal umbilical Doppler parameters have a significantly higher risk for poor outcome. What does this study add? Amniotic fluid discordance in monochorionic diamniotic twin pregnancies that do not meet the criteria for TTTS but with abnormal umbilical Doppler parameters represents an extremely high risk for adverse outcomes regardless of the presence of sIUGR.